Pemanfaatan Rebusan Serai dalam Pengobatan Tradisional untuk Nyeri Kaki di Posyandu Desa Manen Kaleka Tahun 2024 - Anita Anita; Rini Lidia Tamba; Shen Shen Panggabean; Eunike Shine Sitohang; Ramdazani Ramdazani; Nurhidayah Nurhidayah; Febrian Josua Panjaitan; Stevani Trio Saputra; Hasudungan Gultom; Rizal Soekarno Putra; Ario Senjaya; Rusmelia Rusmelia; Lefi Ayarai; Putri Putri; Inul Gacici (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Lemongrass has many benefits that can be processed into processed ingredients in traditional medicine to overcome diseases, especially to relieve leg pain that attacks children and adults. Lemongrass in Manen Kaleka village is quite abundant because it is easy to grow lemongrass in the area. Lemongrass plants are only widely sold in the Manen Kaleka village market only for cooking ingredients and its economic value can be said to be still low because of the level of processing. One of the measures that have been shown to be effective non-pharmacologically to reduce pain is to warm the affected joint. This lemongrass soak can be used in the treatment of pain and relax tense muscles. Plants that have substances as warmers, anti-inflammatories and can smooth blood flow such as lemongrass. The purpose of this activity is to describe the use of lemongrass decoction in traditional medicine for leg pain at the Manen Kaleka Village Posyandu in 2024, as well as to explore its potential benefits for public health.